Adjuvant and neoadjuvant therapy with or without CDK4/6 inhibitors in HR+/HER2- early breast cancer: a systematic review and meta-analysis - Zhang, Zhihao; Zhao, Xin; Chen, Jie (Frontiers in Pharmacology, 2024)
The combination of cyclin-dependent kinases 4/6 (CDK4/6) inhibitors and endocrine therapy is the standard treatment for patients with hormone receptor-positive (HR+)/HER2-negative (HER2-) advanced breast cancer.However, the role of CDK4/6 inhibitors in early breast cancer remains controversial.This study aimed to evaluate the efficacy and safety of CDK4/6 inhibitors combined with endocrine therapy versus endocrine therapy alone in patients with HR+, HER2-early breast cancer. A systematic review of Cochrane, PubMed and EMBASE databases was conducted. The efficacy endpoints of adjuvant therapy were invasive disease-free survival (IDFS), overall survival (OS) and distant relapse-free survival (DRFS). The efficacy endpoint included complete cell cycle arrest (CCCA) and complete pathologic response (PCR) with neoadjuvant therapy. Grade 3/4 adverse events (AEs) were assessed as safety outcomes.Eight randomized controlled trials (RCTs) were included in the study. CDK4/6 inhibitors combined with endocrine therapy showed a significant improvement in IDFS (hazard ratio (HR) = 0.81, 95% confidence interval (CI) = 0.68-0.97, P = 0.024), but not DRFS (HR = 0.84, 95% CI = 0.56-1.29, P = 0.106) or OS (HR = 0.96, 95% CI = 0.77-1.19, P = 0.692) in adjuvant therapy. In the neoadjuvant therapy setting, CDK4/6 inhibitors improved CCCA compared with the control group (RR = 2.08, 95% CI = 1.33-3.26, P =0.001). The risk of 3/4 grade AEs increased significantly with the addition of CDK4/6 inhibitors to endocrine therapy.the addition of CDK4/6 inhibitors in HR+/HER2-early breast cancer patients significantly improved IDFS in adjuvant therapy and CCCA in neoadjuvant.However, CDK4/6 inhibitors also showed significant toxicities during therapy.